A Rare Case of Primary Breast Lymphoma - Priyono, Sasongko Hadi; Effendy, Effendy (http://dharmais.co.id/, 2024)
Introduction: Breast lymphoma (BL) is an uncommon type of extranodal non-Hodgkin lymphoma. Breast lymphoma is challenging to diagnose as its findings are not very specific and usually hard to differentiate from other breast carcinoma. There are no current authorized therapeutic guidelines to date because of the case rarity. In this report, we present a case of detected primary breast lymphoma in a 28-years woman which treated with systemic six cycles of R-CHOP (rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine (Oncovin), prednisone) chemotherapy, the response remained satisfying until the end of the cycle and no complications were reported.Case Presentation: A 28-year-old woman who had primary breast lymphoma, was treated and had a positive recovery. Clinical examination showed a hard, mobile, erythematous, ulcerating, necrotizing mass in the left breast, approximately 35 cm in the largest dimension. Mammae ultrasound revealed a hypoechoic mass located on the outer upper quadrant presumed malignant (BI-RADS 5). A core biopsy was performed, and an immunohistochemistry test revealed the CD45, CD20, and Ki-67 expression were positive, which finally diagnosed the case as a high-grade B-cell non-Hodgkin’s lymphomaResults: The patient was treated with systemic chemotherapy with six cycles of the R-CHOP protocol, which included administration of cyclophosphamide, doxorubicin, vincristine, rituximab, and prednisone. The patient response remained satisfying until the end of the cycle and no complications were reported.